2004
DOI: 10.2527/2004.82113245x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of dietary ractopamine concentration and duration of feeding on growth performance, carcass characteristics, and meat quality of finishing pigs

Abstract: A total of 400 barrows from Dekalb EB and 83 terminal sires mated to 43 and 45 maternal lines were used to evaluate the effects of dietary ractopamine (RAC; Paylean, Elanco Animal Health, Greenfield, IN) concentrations (0, 5, 10, or 20 ppm; as-fed basis) and feeding durations (6 to 34 d) on growth, efficiency, carcass, and meat quality characteristics of finishing pigs. Barrows were weighed and sorted into five weight blocks, each block consisting of 16 pens (five pigs per pen). Weight blocks were allocated to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
69
5
27

Year Published

2007
2007
2014
2014

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 128 publications
(117 citation statements)
references
References 20 publications
16
69
5
27
Order By: Relevance
“…Assim, atuando no metabolismo dos animais como um particionador de nutrientes para funções desejáveis, a ractopamina pode melhorar as taxas de crescimento e a eficiência alimentar de suínos (ARMSTRONG et al, 2004).…”
Section: Resultsunclassified
See 1 more Smart Citation
“…Assim, atuando no metabolismo dos animais como um particionador de nutrientes para funções desejáveis, a ractopamina pode melhorar as taxas de crescimento e a eficiência alimentar de suínos (ARMSTRONG et al, 2004).…”
Section: Resultsunclassified
“…Os aditivos ß-adrenérgicos são uma alternativa nutricional comumente utilizada na produção animal como particionadores de nutrientes, melhorando a retenção de nitrogênio, as taxas de crescimento e a deposição de tecido muscular em detrimento de gordura (ARMSTRONG et al, 2004). Apesar do amplo uso em nutrição animal, pouco é conhecido sobre as implicações da ractopamina como aditivo melhorador de desempenho, especialmente no que diz respeito à sua interação com outros componentes nutricionais.…”
Section: Introductionunclassified
“…Some results indicate no effect of RAC on the visual assessment of marbling in the LM between the 10th and 11th ribs (Watkins et al 1990;Stites et al 1991;Crome et al 1996), or on the extractable lipid content of the LM (Stites et al 1994). Armstrong et al (2004) reported that the visual marbling score for the LM was decreased when RAC was fed for 34 d at 10 and 20 ppm compared with 0 ppm RAC. Conversely, Watkins et al (1990) and Aalhus et al (1990) reported that the LM from RAC-fed pigs received higher marbling scores than pork from control pigs, whereas several other studies observed similar marbling scores between RAC and control pigs (Adeola et al 1990;Crome et al 1996;Stoller et al 2003;Weber et al 2006).…”
Section: Discussionmentioning
confidence: 99%
“…The lower a* values may also be due to the shift of intermediate fibres (Type 2A) to white fibres (Type 2B) (McKeith et al 1988;Anderson et al 1991;Uttaro et al 1993). Armstrong et al (2004) reported that the effect of RAC on colour was dependent on its level and feeding period. They found that L*, a*, and b* values of the loin muscle were not affected by 5 and 10 ppm RAC compared with controls during each feeding period.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation